Black soldier fly (Hermetia illucens) larvae meal for heat-stressed broiler chicken: its effects on gut health, stress biomarkers, and growth performance - Mazlan, Nur Ain Farhanim; Miswan, Nur Alia; Ahmad, Sharmila; Hassim, Hasliza Abu; Jamien, Eddy Shahriza; Wei Ee, Hew; Kumari Ramiah, Suriya; Idrus, Zulkifli (Taylor and Francis Group, 2024)
The study determined the effects of feeding black soldier fly larvae meal (BSFLM) on serum corticosterone (CORT), heat shock protein (HSP) 70, d-lactic acid (DLA), diamine oxidase (DAO) levels, gut health and performance in heat-stressed broiler chickens. Three hundred sixty-day-old male broiler chicks were assigned to BSFLM inclusion at 0% (D0) (12 replicate cages with 10 birds/cage), 5% (D5) (12 replicate cages with 10 birds/cage) or 10% (D10) (12 replicate cages with 10 birds/cage). From days 22 to 35, birds from each dietary group were exposed to either heat stress (heated) at 32 ± 1 °C for 6 h (1100 − 1700 h) or 24 ± 1 °C throughout. There were six replicate cages with 10 birds/cage per diet-temperature subgroup. Diet had no significant effect (p > 0.05) on growth performance or mortality rate. The CORT of the heated DO chickens were elevated (p < 0.05) but not their D5 and D10 counterparts. Diet did not influence HSP70, but the heat challenge increased the expression of the proteins. The unheated D0 birds showed higher (p < 0.05) DLA than the other groups. Irrespective of diet, heat exposure elevated DAO. The heat-stressed D5 and D10 birds had lower (p < 0.05) caecal E.coli and Clostridium spp. than the D0 group. The D10 chickens showed increased caecal Lactobacillus spp. counts compared to the other groups. Heat exposure but not diet was detrimental to intestinal morphology. In conclusion, BSFLM as a feed ingredient may support optimum growth performance and enhance gut health and heat tolerance in broilers.